Investigation of the interaction between hydrogen and irradiation defects in titanium by using positron annihilation spectroscopy. (6th April 2021) - An, Xudong; Zhu, Te; Wan, Mingpan; Li, Yuanhui; Wang, Qianqian; Zhang, Peng; Liu, Jinyang; Song, Yamin; Zhang, Zhaokuan; Wang, Baoyi; Cao, Xingzhong
Abstract: The formation of mono-vacancy, vacancy clusters and hydrogen-vacancy complexes with 30 keV H ion-irradiated pure titanium at different doses and temperatures was measured using by Positron annihilation spectroscopy (PAS). Results show a large number of H m V n clusters and vacancy-like defects in the samples irradiated at for room temperature, and that the formation of H m V n ( m  >  n ) at the sample irradiated at a high dose inhibits the increase of the S parameter. At increased irradiation temperature, the shrinkage of vacancy clusters and the effective open volume of defects decrease the S parameters. The high-temperature irradiation results in decreased vacancy-type defect concentration, and some hydrogen atoms diffuse from the cascade region to the track region, forming a large number of hydrogen-vacancy complexes in the track region. The coincidence Doppler broadening spectroscopy, an element analysis method, used to detect hydrogen in the ion-irradiated pure titanium sample, and results show hydrogen-related peaks in the high-momentum region, which may be due to the information of positron annihilation in the covalent bond formed by the H and the Ti elements. The increased radiation dose and temperature contribute to the formation of the hydrogen vacancy-complex, and the positron annihilation in high-momentum regions easily obtain hydrogen-related information. Highlights: The increased radiation dose and temperature contribute to the formation of the hydrogen vacancy-complex (H m V n ). The formation of H m V n (m > n) at the sample irradiated at a high dose inhibits the increase of the S parameter. Hydrogen-vacancy complexes (H m V n ) formed as hydrogen atoms deposited in the material.